Rambutan-shaped polyacrylamide nanospheres and preparation method and application thereof
Rambutan-shaped polyacrylamide nanospheres were prepared by loading metal copper quantum dots on PAMAM tree macromolecules, which solved the problems of existing microspheres with large particle size and poor temperature and salt resistance, and achieved the preparation of nanoscale microspheres and deep driving effect.
Patent Information
- Application Number
- CN202411629429.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The microspheres prepared in the prior art have large particle sizes and poor temperature and salt resistance, making it difficult to effectively penetrate deep into the reservoir for deep driving.
Rambutan-like polyacrylamide nanospheres were used, which initiate polymerization by heating on PAMAM dendrimers and heating under the protection of inert gas to prepare nanospheres with particle sizes between 10-100 nm.
The preparation of nano-scale polymer microspheres has been achieved, with higher temperature and salt resistance and formation penetration capabilities, and can effectively penetrate deep into the reservoir for deep driving, improving recovery.
Smart Images

Figure CN119119360B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano oil displacement, and particularly relates to rambutan-shaped polyacrylamide nanospheres and a preparation method and application thereof. Background Art
[0002] Uneven water injection profiles will aggravate the heterogeneity of the reservoir, causing the injected water to advance and flow to varying degrees. Reservoir heterogeneity, scouring of injected water, migration of interlayer materials, expansion and dissolution, and other phenomena seriously affect the effect of water injection development in oil fields, resulting in a continuous decrease in recovery. Low permeability reservoirs often fail to inject water due to the complex fracture pore structure and small pore throats. High permeability reservoirs have strong water absorption capacity, so water injection often leads to the appearance of water flow channels in the formation. At present, most oil fields are in the medium and high water content period. In order to improve the recovery rate, that is, to improve the sweep efficiency of injected water and balance the water absorption profile, the main method is to find ways to expand the swept volume of injected water to improve the effect of water injection development. In order to improve the problems existing in the water injection process of low permeability reservoirs, it is necessary to optimize the performance of profile control agents so that they can meet the requirements of deep profile control.
[0003] Practice has proved that focusing on profile control, conducting relevant research on the recovery enhancement technology combining profile control and oil displacement, reducing the oil-water interfacial tension, and increasing the swept volume of injected water have great practical significance for improving the post-waterflooding development benefits of oil fields and improving the final recovery rate. At present, the commonly used profile control technology has achieved remarkable results in the actual application of oil fields, but traditional profile control agents also have some shortcomings. For example, granular profile control agents, although they have high strength and can well block the high permeability layer, are mainly used to improve the seepage situation near the injection well and increase the swept volume near the injection well. Their deep profile control effect is not great. Granular profile control agents often have large particle sizes and are mainly used to block the oil layer near the injection well. However, the residual oil saturation near the injection well is small, and the recovery rate is very low. The injected water will eventually bypass and enter the high permeability layer again. Although the underground cross-linked organic profile control system has the characteristics of mobility and can reach the deep part of the reservoir for profile control, its plugging strength cannot meet the requirements of high permeability formations. After a short period of plugging, it will be broken through by the injected water and has a short effective period. Therefore, based on the actual needs of the later stage of high water-content reservoir development, the development of deep-seated displacement agents that are effective in the long term and have a certain strength has become the core issue currently faced.
[0004] Deep profile control technology refers to the use of various organic and inorganic profile control and water plugging agents such as gel foam and polymer microspheres. These profile control and water plugging agents can penetrate deep into the reservoir, block high permeability reservoirs, force liquids to flow to low permeability reservoirs, and increase the volume of injected water in medium and low permeability reservoirs, thereby improving the recovery rate.
[0005] At present, polymer microspheres mainly have good water absorption and expansion performance, but large particle size, poor temperature and salt resistance, and will be damaged during migration to deep reservoirs, resulting in the polymer microspheres entering shallow formations or poor deep plugging performance. Therefore, the development of nanospheres with high temperature and salt resistance and strong formation penetration ability is the key to improving deep reservoir plugging.
[0006] Quantum dots are a new type of semiconductor nanomaterial, a type of semiconductor nanoparticle composed of II-VI or III-V elements with a radius smaller than or close to the exciton Bohr radius. Due to the influence of quantum size effect and dielectric confinement effect, quantum dots have unique properties, which makes quantum dots have great application potential in the fields of oil extraction and catalysis. The prior art generally directly uses quantum dots as tracers or oil displacement agents, and the application range is relatively narrow. CN115306362A directly uses quantum dots as oil displacement agents, and uses the extremely strong penetration and oil washing effects of quantum dots to penetrate into the rock surface to remove the oil film and improve the oil washing efficiency; however, its cost is relatively high, and it does not have the effect of blocking and regulating displacement. CN115181217A prepares core-shell microspheres with fluorescent tracing function, and introduces fluorescent quantum dots in the process of preparing the core microsphere solution, and then mixes and adsorbs with the shell monomer water to prepare the core-shell nano-microsphere solution. The fluorescent quantum dots are located inside the core-shell fluorescent microspheres and will not detach, thereby improving the subsequent detection accuracy. The quantum dot microspheres are prepared into microspheres of ordinary morphology by direct in-situ polymerization process, and only the tracer function of quantum dots is used for detection, and the plugging and flooding effect is limited. The fluorescent microspheres prepared by CN117736722A, CN115247060A, etc. have smooth surfaces and cannot be used as flooding agents. Summary of the invention
[0007] In order to solve the technical problems that microspheres prepared in the prior art have large particle size and poor temperature and salt resistance, the present invention provides a rambutan-shaped polyacrylamide nanosphere and a preparation method and application thereof.
[0008] In order to achieve the above object, the present invention adopts the following technical scheme:
[0009] A method for preparing rambutan-shaped polyacrylamide nanospheres comprises the following steps:
[0010] (1) adding PAMAM to a copper quantum dot solution, performing ultrasonic dispersion, and obtaining PAMAM loaded with copper quantum dots after drying; the mass ratio of the copper quantum dots to PAMAM is (0.001-0.05):1;
[0011] (2) dispersing the PAMAM loaded with metal copper quantum dots and a surfactant in an organic solvent and stirring evenly to obtain a premixed solution;
[0012] (3) Adding acrylamide and acrylic acid monomers and a cross-linking agent to the premixed solution and stirring evenly; and heating the premixed solution under the protection of an inert gas to react to obtain rambutan-like polyacrylamide nanospheres.
[0013] In the previous work (CN118580443A), the inventor used silica of different particle sizes as reinforcing fillers and prepared polyacrylamide microspheres by dispersion polymerization, which improved the heat resistance and salt resistance of the microspheres to a certain extent. However, the microspheres have a large particle size, a relatively smooth surface, weak interaction between microspheres, and limited blocking and regulation effects. Subsequently, the inventor used mesoporous microspheres as core materials and embedded copper oxide quantum dots using the larger pore structure of the mesoporous microspheres to prepare polyacrylamide microspheres with a litchi-like structure. However, the above-mentioned polymer microspheres prepared using traditional azo substances as initiators still have a large particle size and low migration and blocking capabilities. And the litchi-shaped appearance has short protrusions and limited interactive blocking capabilities. In order to solve the above problems, the present invention introduces a dendritic PAMAM (polyamide-amine) polymer with multiple active groups as a matrix to prepare PAMAM loaded with metallic copper quantum dots.
[0014] PAMAM is a typical dendrimer. Compared with other traditional dendrimers, PAMAM has a large number of surface functional groups, intramolecular cavities and nanometer-scale dimensions, which provide a basis for loading copper quantum dots. Since the hydrocarbon chains in the PAMAM dendrimer are lipophilic groups, but the carboxyl and amino groups it contains are hydrophilic groups, it not only has the effect of solubilization and stabilization, but can also combine with copper quantum dots through electrostatic adsorption; on the other hand, the presence of a large number of cavities on the surface and inside of PAMAM also helps to load copper quantum dots.
[0015] Compared with copper oxide quantum dots, metal copper quantum dots are more active; and due to their large surface area to volume ratio, the copper atoms exposed on the surface can provide a large number of active sites, thereby enhancing the catalytic activity. The unpaired electrons of metal copper quantum dots can be conjugated with the double bonds of acrylamide monomers, and free radicals can be generated to initiate polymerization without chemical initiators. Under heating conditions, the initiation rate is accelerated while the monomer conversion rate is also accelerated. Compared with the previous technology of loading copper oxide quantum dots with large-particle-size mesoporous microspheres and preparing microspheres with azo substances as initiators, the nanospheres prepared by loading copper quantum dots with PAMAM as a matrix to initiate polymerization in the present invention have a smaller particle size, and nanoscale polymer microspheres are truly prepared. Moreover, the present invention does not need to add an initiator, and since the monomer undergoes polymerization reaction on the surface of metal copper quantum dots, one end of the quantum dots is combined with PAMAM, and the catalytic activity is low; while the catalytic activity of the exposed end is higher. Therefore, the characteristics of spherical particles lead to uneven polymerization rates. Compared with copper oxide quantum dots, they can promote the formation of irregular morphology of nanospheres, and finally prepare rambutan-like polyacrylamide nanospheres.
[0016] Furthermore, the PAMAM in step (1) is a 4-10 generation PAMAM. The present invention uses PAMAM dendrimers of various generations of ethylenediamine core synthesized using ethylenediamine (EDA) and methyl acrylate (MA) as raw materials. The outer layers of PAMAM dendrimers of different generations have a large number of hydrophilic groups such as ester groups, amino groups or carboxyl groups, while the hydrocarbon chains inside are lipophilic groups, so polyamide-amine has the dual functions of a carrier and a surfactant. The present invention does not require the use of a mercaptosilane coupling agent to modify the quantum dots. The hydrogen bonding between the PAMAM surface active groups and the metal copper quantum dots reduces the surface energy of the metal copper quantum dots and improves their dispersibility. On the other hand, it can prevent the metal copper quantum dots from being oxidized or agglomerated, thereby improving the stability of the metal copper quantum dots in the solvent.
[0017] Furthermore, the copper metal quantum dot solution in step (1) is a chloroform solution of copper metal quantum dots.
[0018] Furthermore, in step (1), the ultrasonic power is 100-200 W, and the ultrasonic temperature is 35-45° C. Ultrasonic vibration can generate strong shear force and eddy current in the liquid, greatly increasing the contact ability between the PAMAM surface active groups and the metal copper quantum dots, and promoting the formation of chemical bonds and electrostatic adsorption forces.
[0019] Furthermore, in step (2), the organic solvent is a mixed solution of ethanol and ethyl acetate; and the stirring time is 1-2h.
[0020] Furthermore, in step (2), the surfactant is polyvinyl pyrrolidone. Since the outer layer of the PAMAM dendrimer has a large number of hydrophilic groups such as ester groups, amino groups or carboxyl groups, it exhibits strong hydrophilicity. In order to improve the dispersion performance of PAMAM in organic solvents, the present invention deliberately disperses the PAMAM loaded with metal copper quantum dots and the surfactant used in the acrylamide polymerization process in an organic solvent in advance to prepare a premixed solution; polar molecules such as acrylamide and acrylic acid monomers, N, N-methylenebisacrylamide crosslinking agents, etc. can be prevented from combining with the metal copper quantum dots in advance to prevent affecting the stability of the quantum dots in the solution and the dispersion of the PAMAM loaded with metal copper quantum dots.
[0021] Furthermore, in step (3), the crosslinking agent is N,N-methylenebisacrylamide; the temperature of the heating reaction is 55-75°C, and the time is 2-6h. Furthermore, the reaction temperature is 60-70°C. If the reaction temperature is too low, it is not conducive to the initiation of polymerization of the metal copper quantum dots, and the reaction rate is low; if the reaction temperature is too high, the reaction heat cannot be dispersed in time, and implosion is likely to occur, which is not conducive to the formation of the rambutan morphology.
[0022] Furthermore, the amounts of PAMAM, surfactant, acrylamide, acrylic acid, and crosslinking agent loaded with metal copper quantum dots are respectively: 1 part of PAMAM loaded with metal copper quantum dots, 1-3 parts of surfactant, 10-15 parts of acrylamide, 5-10 parts of acrylic acid, and 1-3 parts of crosslinking agent. Furthermore, the crosslinking agent is 1.8-2.4 parts, and moderate crosslinking can not only improve the strength of the nanospheres, but also improve the elasticity of the nanospheres, so that it can take into account both the rigid blocking and elastic displacement capabilities.
[0023] Further, the average particle size of the rambutan-like polyacrylamide nanospheres is 10-100nm; further, the average particle size of the rambutan-like polyacrylamide nanospheres is 10-60nm; in particular, the average particle size of the rambutan-like polyacrylamide nanospheres is 10-50nm or 10-30nm. The particle size of the rambutan-like polyacrylamide nanospheres can be adjusted by adjusting the PAMAM generation number and the polymerization reaction time. On the basis of ensuring the mechanical properties of the rambutan-like polyacrylamide nanospheres, their plugging and oil displacement capabilities are improved.
[0024] On the other hand, the present invention also provides an application of rambutan-shaped polyacrylamide nanospheres as a profile control and oil recovery agent. Acrylamide-based polymers are a type of synthetic polymer used to enhance oil recovery. They have excellent rheological properties and are one of the most commonly used polymers in oil recovery applications. Due to the presence of a strong hydrophilic group, the amide group, the polyacrylamide nanospheres have good water absorption and swelling properties. They can absorb water and swell deep in the reservoir, seal at the gaps, increase the swept volume of the injected fluid, and thus improve the recovery rate. In order to enhance the stability of the polymer nanospheres in the harsh environment of high temperature and high salt in the reservoir, the main monomer acrylamide (AM) and the functional monomer acrylic acid (AA) are copolymerized, and an appropriate amount of a cross-linking agent is added to prepare acrylamide-based quantum dot copolymer nanospheres with a cross-linked structure.
[0025] The rambutan-shaped polyacrylamide nanospheres prepared by this method are greatly reduced in size relative to the lychee-shaped microspheres previously developed by the inventors, and are also much smaller than the formation pore throat size, fully meeting the requirements of deep flooding technology, and can smoothly reach the deep reservoir. Compared with linear polymers, the viscosity of the rambutan-shaped polyacrylamide nanosphere dispersion system is very low, and has good hydration expansion performance. After reaching the deep reservoir, the nanospheres that continuously absorb water and expand are retained at the large pore throats to form a blockage, thereby achieving the flow diversion effect, not only increasing the swept volume of the injected water, but also achieving the effect of deep profile adjustment. Moreover, the surface of the rambutan-shaped polyacrylamide nanospheres prepared by the present invention presents the morphology of rambutan, relative to the nanospheres with smooth outer surfaces, not only can the expansion and rupture phenomenon after water absorption be avoided, but also the interaction force between the nanospheres is enhanced, and the plugging effect is better. At the same time, as the nanospheres absorb water and expand, the long "tentacles" similar to rambutan on their appearance also expand therewith, and the expanded "tentacles" play the role of cross-linked nanospheres, which can play a better plugging effect.
[0026] Beneficial effects:
[0027] The nanospheres prepared by the polymerization of copper quantum dots loaded on PAMAM as a matrix in the present invention have a smaller particle size, and nanoscale polymer microspheres are truly prepared. Moreover, the present invention does not need to add an initiator, and because the monomer undergoes polymerization reaction on the surface of the metal copper quantum dots, one end of the quantum dots is combined with PAMAM, and the catalytic activity is low; the catalytic activity of the exposed end is higher. Therefore, the characteristics of the spherical particles lead to uneven polymerization rates. Compared with copper oxide quantum dots, they can promote the formation of irregular morphology of nanospheres, and finally prepare rambutan-like polyacrylamide nanospheres. The viscosity of the rambutan-like polyacrylamide nanosphere dispersion system is very low, and it has good hydration and expansion properties. After reaching the deep part of the reservoir, the nanospheres that continuously absorb water and expand are retained at the large pore throats to form a blockage, thereby achieving a flow diversion effect, which not only increases the swept volume of the injected water, but also achieves the effect of deep profile adjustment. Moreover, the surface of the rambutan-like polyacrylamide nanospheres prepared by the present invention presents the morphology of rambutan, which can not only avoid the expansion and rupture phenomenon after water absorption, but also enhance the interaction force between the nanospheres, and the plugging effect is better. At the same time, as the nanospheres absorb water and swell, the expanded "tentacles" play the role of cross-linking the nanospheres, which can achieve a better blocking effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a scanning electron micrograph of polyacrylamide nanospheres prepared in Example 11;
[0029] Figure 2 This is a scanning electron microscope image of polyacrylamide nanospheres prepared in Comparative Example 1;
[0030] Figure 3 This is a scanning electron microscope image of the polyacrylamide nanospheres prepared in Comparative Example 2. DETAILED DESCRIPTION
[0031] To make the purpose, technical solution and advantages of the present invention clearer, the technical solution in the embodiment of the present invention will be clearly and completely described below in combination with the embodiment of the present invention. Obviously, the described embodiment is a part of the embodiment of the present invention, but not all of the embodiments. The components of the embodiment of the present invention can be arranged and designed in various different configurations.
[0032] Example 1
[0033] A method for preparing rambutan-shaped polyacrylamide nanospheres comprises the following steps:
[0034] (1) PAMAM was added to a chloroform solution of metal copper quantum dots with an average particle size of 3 nm, ultrasonically dispersed, and dried to obtain PAMAM loaded with metal copper quantum dots; the mass ratio of the metal copper quantum dots to PAMAM was 0.003:1; the PAMAM was an 8th generation PAMAM; the ultrasonic power was 100 W, and the ultrasonic temperature was 45°C;
[0035] (2) Dispersing PAMAM loaded with metal copper quantum dots and surfactant polyvinyl pyrrolidone in an organic solvent and stirring evenly to obtain a premixed solution; the organic solvent is a mixed solution of ethanol and ethyl acetate; the stirring time is 1 hour;
[0036] (3) Add acrylamide and acrylic acid monomers and a cross-linking agent N,N-methylenebisacrylamide to the premixed solution and stir evenly; and under the protection of an inert gas, heat the reaction to obtain rambutan-shaped polyacrylamide nanospheres; the heating reaction temperature is 60°C and the time is 6 h; the amounts of PAMAM loaded with metal copper quantum dots, surfactant, acrylamide, acrylic acid, and cross-linking agent are as follows by mass: 1 part of PAMAM loaded with metal copper quantum dots, 1 part of surfactant, 10 parts of acrylamide, 5 parts of acrylic acid, and 1.8 parts of cross-linking agent.
[0037] Example 2
[0038] A method for preparing rambutan-shaped polyacrylamide nanospheres comprises the following steps:
[0039] (1) PAMAM was added to a chloroform solution of metal copper quantum dots with an average particle size of 3 nm, ultrasonically dispersed, and dried to obtain PAMAM loaded with metal copper quantum dots; the mass ratio of the metal copper quantum dots to PAMAM was 0.05:1; the PAMAM was an 8th generation PAMAM; the ultrasonic power was 200 W, and the ultrasonic temperature was 35°C;
[0040] (2) Dispersing PAMAM loaded with metal copper quantum dots and surfactant polyvinyl pyrrolidone in an organic solvent and stirring evenly to obtain a premixed solution; the organic solvent is a mixed solution of ethanol and ethyl acetate; the stirring time is 2 hours;
[0041] (3) Add acrylamide and acrylic acid monomers and a cross-linking agent N,N-methylenebisacrylamide to the premixed solution and stir evenly; and heat the reaction under the protection of inert gas to obtain rambutan-shaped polyacrylamide nanospheres; the heating reaction temperature is 70°C and the time is 2.6 h; the amounts of PAMAM loaded with metal copper quantum dots, surfactant, acrylamide, acrylic acid, and cross-linking agent are as follows by mass: 1 part of PAMAM loaded with metal copper quantum dots, 3 parts of surfactant, 15 parts of acrylamide, 10 parts of acrylic acid, and 2.4 parts of cross-linking agent.
[0042] Example 3
[0043] A method for preparing rambutan-shaped polyacrylamide nanospheres comprises the following steps:
[0044] (1) PAMAM was added to a chloroform solution of metal copper quantum dots with an average particle size of 3 nm, ultrasonically dispersed, and dried to obtain PAMAM loaded with metal copper quantum dots; the mass ratio of the metal copper quantum dots to PAMAM was 0.05:1; the PAMAM was an 8th generation PAMAM; the ultrasonic power was 100 W, and the ultrasonic temperature was 35°C;
[0045] (2) Dispersing PAMAM loaded with metal copper quantum dots and surfactant polyvinyl pyrrolidone in an organic solvent and stirring evenly to obtain a premixed solution; the organic solvent is a mixed solution of ethanol and ethyl acetate; the stirring time is 2 hours;
[0046] (3) Add acrylamide and acrylic acid monomers and a cross-linking agent N,N-methylenebisacrylamide to the premixed solution and stir evenly; and heat the reaction under the protection of inert gas to obtain rambutan-shaped polyacrylamide nanospheres; the heating reaction temperature is 70°C and the time is 4 hours; the amounts of PAMAM loaded with metal copper quantum dots, surfactant, acrylamide, acrylic acid, and cross-linking agent are as follows by mass: 1 part of PAMAM loaded with metal copper quantum dots, 3 parts of surfactant, 10 parts of acrylamide, 10 parts of acrylic acid, and 2.4 parts of cross-linking agent.
[0047] Example 4
[0048] A method for preparing rambutan-shaped polyacrylamide nanospheres comprises the following steps:
[0049] (1) PAMAM was added to a chloroform solution of copper quantum dots having an average particle size of 3 nm, and ultrasonically dispersed, and dried to obtain PAMAM loaded with copper quantum dots; the mass ratio of the copper quantum dots to PAMAM was 0.01:1; the PAMAM was of the eighth generation; the ultrasonic power was 120 W, and the ultrasonic temperature was 42°C;
[0050] (2) PAMAM loaded with metal copper quantum dots and surfactant polyvinyl pyrrolidone are dispersed in an organic solvent and stirred evenly to obtain a premixed solution; the organic solvent is a mixed solution of ethanol and ethyl acetate; the stirring time is 1.3 h;
[0051] (3) Add acrylamide and acrylic acid monomers and cross-linking agent N,N-methylenebisacrylamide to the premixed solution and stir evenly; and heat the reaction under the protection of inert gas to obtain rambutan-shaped polyacrylamide nanospheres; the heating reaction temperature is 64°C and the time is 4 h; the amounts of PAMAM loaded with metal copper quantum dots, surfactant, acrylamide, acrylic acid, and cross-linking agent are as follows by mass: 1 part of PAMAM loaded with metal copper quantum dots, 1.6 parts of surfactant, 12 parts of acrylamide, 6 parts of acrylic acid, and 2 parts of cross-linking agent.
[0052] Example 5
[0053] A method for preparing rambutan-shaped polyacrylamide nanospheres comprises the following steps:
[0054] (1) PAMAM was added to a chloroform solution of metal copper quantum dots with an average particle size of 3 nm, ultrasonically dispersed, and dried to obtain PAMAM loaded with metal copper quantum dots; the mass ratio of the metal copper quantum dots to PAMAM was 0.04:1; the PAMAM was 8th generation PAMAM; the ultrasonic power was 170 W, and the ultrasonic temperature was 38°C;
[0055] (2) PAMAM loaded with metal copper quantum dots and surfactant polyvinyl pyrrolidone are dispersed in an organic solvent and stirred evenly to obtain a premixed solution; the organic solvent is a mixed solution of ethanol and ethyl acetate; the stirring time is 1.7 h;
[0056] (3) Add acrylamide and acrylic acid monomers and cross-linking agent N,N-methylenebisacrylamide to the premixed solution and stir evenly; and heat the reaction under the protection of inert gas to obtain rambutan-shaped polyacrylamide nanospheres; the heating reaction temperature is 66°C and the time is 3 h; the amounts of PAMAM loaded with metal copper quantum dots, surfactant, acrylamide, acrylic acid, and cross-linking agent are as follows by mass: 1 part of PAMAM loaded with metal copper quantum dots, 2.5 parts of surfactant, 14 parts of acrylamide, 8 parts of acrylic acid, and 2.2 parts of cross-linking agent.
[0057] Example 6
[0058] A method for preparing rambutan-shaped polyacrylamide nanospheres comprises the following steps:
[0059] (1) PAMAM was added to a chloroform solution of metal copper quantum dots with an average particle size of 3 nm, ultrasonically dispersed, and dried to obtain PAMAM loaded with metal copper quantum dots; the mass ratio of the metal copper quantum dots to PAMAM was 0.02:1; the PAMAM was an 8th generation PAMAM; the ultrasonic power was 160 W, and the ultrasonic temperature was 39°C;
[0060] (2) PAMAM loaded with metal copper quantum dots and surfactant polyvinyl pyrrolidone are dispersed in an organic solvent and stirred evenly to obtain a premixed solution; the organic solvent is a mixed solution of ethanol and ethyl acetate; the stirring time is 1.4 h;
[0061] (3) Add acrylamide and acrylic acid monomers and cross-linking agent N,N-methylenebisacrylamide to the premixed solution and stir evenly; and under the protection of inert gas, heat the reaction to obtain rambutan-shaped polyacrylamide nanospheres; the heating reaction temperature is 69°C and the time is 4.2 h; the amounts of PAMAM loaded with metal copper quantum dots, surfactant, acrylamide, acrylic acid, and cross-linking agent are as follows by mass: 1 part of PAMAM loaded with metal copper quantum dots, 1.3 parts of surfactant, 13 parts of acrylamide, 7 parts of acrylic acid, and 1.9 parts of cross-linking agent.
[0062] Example 7
[0063] A method for preparing rambutan-shaped polyacrylamide nanospheres comprises the following steps:
[0064] (1) PAMAM was added to a chloroform solution of metal copper quantum dots with an average particle size of 3 nm, ultrasonically dispersed, and dried to obtain PAMAM loaded with metal copper quantum dots; the mass ratio of the metal copper quantum dots to PAMAM was 0.03:1; the PAMAM was an 8th generation PAMAM; the ultrasonic power was 150 W, and the ultrasonic temperature was 42°C;
[0065] (2) Dispersing PAMAM loaded with metal copper quantum dots and surfactant polyvinyl pyrrolidone in an organic solvent and stirring evenly to obtain a premixed solution; the organic solvent is a mixed solution of ethanol and ethyl acetate; the stirring time is 1.5 h;
[0066] (3) Add acrylamide and acrylic acid monomers and cross-linking agent N,N-methylenebisacrylamide to the premixed solution and stir evenly; and heat the reaction under the protection of inert gas to obtain rambutan-shaped polyacrylamide nanospheres; the heating reaction temperature is 55°C and the time is 3.5 h; the amounts of PAMAM loaded with metal copper quantum dots, surfactant, acrylamide, acrylic acid, and cross-linking agent are as follows by mass: 1 part of PAMAM loaded with metal copper quantum dots, 2 parts of surfactant, 13 parts of acrylamide, 7 parts of acrylic acid, and 2 parts of cross-linking agent.
[0067] Example 8
[0068] A method for preparing rambutan-shaped polyacrylamide nanospheres comprises the following steps:
[0069] (1) PAMAM was added to a chloroform solution of metal copper quantum dots with an average particle size of 3 nm, ultrasonically dispersed, and dried to obtain PAMAM loaded with metal copper quantum dots; the mass ratio of the metal copper quantum dots to PAMAM was 0.03:1; the PAMAM was an 8th generation PAMAM; the ultrasonic power was 150 W, and the ultrasonic temperature was 42°C;
[0070] (2) Dispersing PAMAM loaded with metal copper quantum dots and surfactant polyvinyl pyrrolidone in an organic solvent and stirring evenly to obtain a premixed solution; the organic solvent is a mixed solution of ethanol and ethyl acetate; the stirring time is 1.5 h;
[0071] (3) Add acrylamide and acrylic acid monomers and cross-linking agent N,N-methylenebisacrylamide to the premixed solution and stir evenly; and heat the reaction under the protection of inert gas to obtain rambutan-shaped polyacrylamide nanospheres; the heating reaction temperature is 75°C and the time is 3.5 h; the amounts of PAMAM loaded with metal copper quantum dots, surfactant, acrylamide, acrylic acid, and cross-linking agent are as follows by mass: 1 part of PAMAM loaded with metal copper quantum dots, 2 parts of surfactant, 13 parts of acrylamide, 7 parts of acrylic acid, and 2 parts of cross-linking agent.
[0072] Example 9
[0073] A method for preparing rambutan-shaped polyacrylamide nanospheres comprises the following steps:
[0074] (1) PAMAM was added to a chloroform solution of metal copper quantum dots with an average particle size of 3 nm, ultrasonically dispersed, and dried to obtain PAMAM loaded with metal copper quantum dots; the mass ratio of the metal copper quantum dots to PAMAM was 0.03:1; the PAMAM was an 8th generation PAMAM; the ultrasonic power was 150 W, and the ultrasonic temperature was 42°C;
[0075] (2) Dispersing PAMAM loaded with metal copper quantum dots and surfactant polyvinyl pyrrolidone in an organic solvent and stirring evenly to obtain a premixed solution; the organic solvent is a mixed solution of ethanol and ethyl acetate; the stirring time is 1.5 h;
[0076] (3) Add acrylamide and acrylic acid monomers and a cross-linking agent N,N-methylenebisacrylamide to the premixed solution and stir evenly; and heat the reaction under the protection of inert gas to obtain rambutan-shaped polyacrylamide nanospheres; the heating reaction temperature is 66°C and the reaction time is 3.5 h; the amounts of PAMAM loaded with metal copper quantum dots, surfactant, acrylamide, acrylic acid, and cross-linking agent are as follows by mass: 1 part of PAMAM loaded with metal copper quantum dots, 2 parts of surfactant, 13 parts of acrylamide, 7 parts of acrylic acid, and 1 part of cross-linking agent.
[0077] Example 10
[0078] A method for preparing rambutan-shaped polyacrylamide nanospheres comprises the following steps:
[0079] (1) PAMAM was added to a chloroform solution of metal copper quantum dots with an average particle size of 3 nm, ultrasonically dispersed, and dried to obtain PAMAM loaded with metal copper quantum dots; the mass ratio of the metal copper quantum dots to PAMAM was 0.03:1; the PAMAM was an 8th generation PAMAM; the ultrasonic power was 150 W, and the ultrasonic temperature was 42°C;
[0080] (2) Dispersing PAMAM loaded with metal copper quantum dots and surfactant polyvinyl pyrrolidone in an organic solvent and stirring evenly to obtain a premixed solution; the organic solvent is a mixed solution of ethanol and ethyl acetate; the stirring time is 1.5 h;
[0081] (3) Add acrylamide and acrylic acid monomers and cross-linking agent N,N-methylenebisacrylamide to the premixed solution and stir evenly; and heat the reaction under the protection of inert gas to obtain rambutan-shaped polyacrylamide nanospheres; the heating reaction temperature is 66°C and the time is 3.5 h; the amounts of PAMAM loaded with metal copper quantum dots, surfactant, acrylamide, acrylic acid, and cross-linking agent are as follows by mass: 1 part of PAMAM loaded with metal copper quantum dots, 2 parts of surfactant, 13 parts of acrylamide, 7 parts of acrylic acid, and 3 parts of cross-linking agent.
[0082] Embodiment 11
[0083] A method for preparing rambutan-shaped polyacrylamide nanospheres comprises the following steps:
[0084] (1) PAMAM was added to a chloroform solution of metal copper quantum dots with an average particle size of 3 nm, ultrasonically dispersed, and dried to obtain PAMAM loaded with metal copper quantum dots; the mass ratio of the metal copper quantum dots to PAMAM was 0.03:1; the PAMAM was an 8th generation PAMAM; the ultrasonic power was 150 W, and the ultrasonic temperature was 42°C;
[0085] (2) Dispersing PAMAM loaded with metal copper quantum dots and surfactant polyvinyl pyrrolidone in an organic solvent and stirring evenly to obtain a premixed solution; the organic solvent is a mixed solution of ethanol and ethyl acetate; the stirring time is 1.5 h;
[0086] (3) Add acrylamide and acrylic acid monomers and cross-linking agent N,N-methylenebisacrylamide to the premixed solution and stir evenly; and under the protection of inert gas, heat the reaction to obtain rambutan-shaped polyacrylamide nanospheres; the heating reaction temperature is 66°C and the reaction time is 3.5 h; the amounts of PAMAM loaded with metal copper quantum dots, surfactant, acrylamide, acrylic acid, and cross-linking agent are as follows by mass: 1 part of PAMAM loaded with metal copper quantum dots, 2 parts of surfactant, 13 parts of acrylamide, 7 parts of acrylic acid, and 2 parts of cross-linking agent.
[0087] Comparative Example 1
[0088] The preparation process is basically the same as that of Example 11, except that PAMAM is not added in step (1), and the metallic copper quantum dots are directly ultrasonically dispersed (i.e., no PAMAM matrix is added in the entire process); and the amounts of metallic copper quantum dots, surfactant, acrylamide, acrylic acid, and crosslinking agent used are the same as those in Example 11.
[0089] Comparative Example 2
[0090] A method for preparing rambutan-shaped polyacrylamide nanospheres comprises the following steps:
[0091] (1) PAMAM was added to a chloroform solution of metal copper quantum dots with an average particle size of 3 nm, ultrasonically dispersed, and dried to obtain PAMAM loaded with metal copper quantum dots; the mass ratio of the metal copper quantum dots to PAMAM was 0.03:1; the PAMAM was an 8th generation PAMAM; the ultrasonic power was 150 W, and the ultrasonic temperature was 42°C;
[0092] (2) Dispersing the PAMAM loaded with metal copper quantum dots in an organic solvent and stirring evenly to obtain a premixed solution; the organic solvent is a mixed solution of ethanol and ethyl acetate; the stirring time is 1.5 h;
[0093] (3) Add surfactant polyvinyl pyrrolidone, acrylamide and acrylic acid monomers, and cross-linking agent N,N-methylenebisacrylamide to the premixed solution and stir evenly; and heat the reaction under the protection of inert gas to obtain rambutan-like polyacrylamide nanospheres; the heating reaction temperature is 66°C and the reaction time is 3.5 h; the amounts of PAMAM loaded with metal copper quantum dots, surfactant, acrylamide, acrylic acid, and cross-linking agent are as follows by mass: 1 part of PAMAM loaded with metal copper quantum dots, 2 parts of surfactant, 13 parts of acrylamide, 7 parts of acrylic acid, and 2 parts of cross-linking agent.
[0094] Comparative Example 3
[0095] The preparation process is basically the same as that of Example 11, except that the mass ratio of metal copper quantum dots to PAMAM is 0.1:1.
[0096] Performance Test:
[0097] The rambutan-like polyacrylamide nanospheres prepared in Examples 1-11 and Comparative Examples 1-3 were dispersed in white oil, and their initial particle sizes were determined by laser particle size analyzer. The nanospheres prepared in Examples 1-11 and Comparative Examples 1-3 were then dispersed in simulated formation water with a mineralization of 30,000 mg / L, and expanded at 80° C. for different time periods, and their expansion multiples were determined. The results are shown in Table 1.
[0098] Low permeability cores were selected for evaluation of oil displacement effect: the cores were first saturated with simulated formation water to determine their pore volume; then the cores were saturated with simulated crude oil; the cores were displaced with simulated formation water until the outlet end stopped producing oil, and the recovery factor A was determined; rambutan-like polyacrylamide nanosphere dispersion was injected into the cores and placed at 65°C for 5 days; the cores were displaced with simulated formation water again until the outlet end stopped producing oil, and the recovery factor B was determined; the recovery factor increase was C (%) = (BA) / AX 100%, and the results are shown in Table 1.
[0099]
[0100] Depend on Figure 1 It can be seen that the present invention has prepared rambutan-shaped polyacrylamide nanospheres, which have long "tentacles" similar to rambutan on the surface. The formation of the above structure increases the specific surface area of the nanospheres. During the water absorption and swelling process, the larger specific surface area can effectively disperse the internal stress and prevent stress concentration from causing the nanospheres to rupture; moreover, the "tentacle" structure after water absorption and swelling is conducive to mutual entanglement, improving the plugging rate, and thus improving the oil displacement efficiency. Figure 2 It shows that the comparative example 1 does not add PAMAM which has the function of surfactant and carrier, resulting in poor dispersion of metallic copper quantum dots, unable to play the role of nucleating agent, unable to exert the characteristics of spherical particles, unable to form rambutan-shaped polyacrylamide nanospheres, and only a small number of protrusions on the surface of the spheres; and the morphology of the spheres is extremely irregular, and agglomeration occurs. Since the outer layer of the PAMAM dendritic macromolecules has a large number of hydrophilic groups such as ester groups, amino groups or carboxyl groups, and the hydrocarbon chains inside are lipophilic groups; therefore, PAMAM exhibits strong hydrophilicity. In order to improve the dispersion properties of PAMAM loaded with metallic copper quantum dots, the surfactant commonly used in the polymerization process of nanospheres needs to be dispersed in an organic solvent in advance with the PAMAM loaded with metallic copper quantum dots to prevent PAMAM from agglomerating or even settling. Figure 3 It can be seen that in Comparative Example 2, the surfactant and the PAMAM loaded with metal copper quantum dots were not dispersed in the organic solvent in advance, and the spheres formed were very irregular and agglomeration also occurred. At the same time, it can be seen from Comparative Example 3 that due to the high activity of the metal copper quantum dots, there is a strong quantum dot effect. When too much metal copper quantum dots are added, it is not only not conducive to dispersion, but also causes a large number of quantum dots to adhere to the outer surface of PAMAM, affecting the expansion stability of the nanospheres and the improvement of oil displacement efficiency.
[0101] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing rambutan-shaped polyacrylamide nanospheres, characterized in that: The following steps are involved: (1) adding PAMAM to a copper quantum dot solution, performing ultrasonic dispersion, and obtaining PAMAM loaded with copper quantum dots after drying; the mass ratio of the copper quantum dots to PAMAM is (0.001-0.05):1; (2) dispersing the PAMAM loaded with metal copper quantum dots and a surfactant in an organic solvent, stirring evenly, and obtaining a premixed solution; the organic solvent is a mixed solution of ethanol and ethyl acetate; and the surfactant is polyvinyl pyrrolidone; (3) Add acrylamide and acrylic acid monomers and a cross-linking agent to the premixed solution and stir evenly; and heat the solution under the protection of an inert gas to obtain rambutan-like polyacrylamide nanospheres; the heating reaction temperature is 55-75°C and the time is 2-6 hours; The crosslinking agent is N,N-methylenebisacrylamide; the amounts of PAMAM loaded with metal copper quantum dots, surfactant, acrylamide, acrylic acid and crosslinking agent are respectively as follows by mass: 1 part of PAMAM loaded with metal copper quantum dots, 1-3 parts of surfactant, 10-15 parts of acrylamide, 5-10 parts of acrylic acid and 1-3 parts of crosslinking agent.
2. The method for preparing rambutan-shaped polyacrylamide nanospheres according to claim 1, characterized in that: The PAMAM in step (1) is a 4-10 generation PAMAM.
3. The method for preparing rambutan-shaped polyacrylamide nanospheres according to claim 1, characterized in that: The metallic copper quantum dot solution in step (1) is a chloroform solution of metallic copper quantum dots.
4. The method for preparing rambutan-shaped polyacrylamide nanospheres according to claim 1, characterized in that: In step (1), the ultrasonic power is 100-200 W, and the ultrasonic temperature is 35-45° C.
5. The method for preparing rambutan-shaped polyacrylamide nanospheres according to claim 1, characterized in that: The stirring time in step (2) is 1-2 h.
6. A rambutan-shaped polyacrylamide nanosphere, characterized in that: The rambutan-shaped polyacrylamide nanospheres are prepared by the preparation method of any one of claims 1 to 5.
7. The rambutan-shaped polyacrylamide nanosphere according to claim 6, characterized in that: The average particle size of the rambutan-shaped polyacrylamide nanospheres is 10-100 nm.
8. Use of the rambutan-shaped polyacrylamide nanospheres as claimed in claim 6 or 7 as a profile control and oil displacement agent.
Citation Information
Patent Citations
Preparation method of core-shell type fluorescent microsphere profile control and plugging agent applied to offshore oilfield high-permeability reservoir based on quantum dots
CN115181217A
Quantum dot light-emitting film, preparation and application of quantum dot light-emitting film in white-light Mini-LED device
CN115247060A
Application of quantum dots in unconventional oil reservoir exploitation, oil-displacing agent and method for increasing yield by using oil-displacing agent
CN115306362A
High-brightness and high-stability water-soluble quantum dot fluorescent microsphere and preparation method thereof
CN117736722A
Temperature-resistant and salt-resistant polymer microsphere and preparation method thereof
CN118580443A